2013
DOI: 10.1007/s00432-012-1364-2
|View full text |Cite
|
Sign up to set email alerts
|

Survival of infiltrative hepatocellular carcinoma patients with preserved hepatic function after treatment with transarterial chemoembolization

Abstract: In carefully selected patients with preserved hepatic function and good performance, TACE may achieve long-term survival of infiltrative HCC patients with major PVT without parasitic supply. However, the risk of morbidity and immediate mortality after TACE should be considered to select subjects for the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 24 publications
5
26
0
1
Order By: Relevance
“…For this reason, although TACE is generally accepted as the only available treatment option, its efficacy for the treatment of infiltrative HCC has rarely been studied. However, Kneuertz et al (5) and Jang et al (23) have recently reported that TACE is both safe and feasible in selected patients with infiltrative HCC.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, although TACE is generally accepted as the only available treatment option, its efficacy for the treatment of infiltrative HCC has rarely been studied. However, Kneuertz et al (5) and Jang et al (23) have recently reported that TACE is both safe and feasible in selected patients with infiltrative HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Sorafenib is recommended for the treatment of advanced and unresectable HCC (12). However, other modalities, such as transarterial chemoembolization (TACE) or transarterial radioembolization using yttrium-90 microspheres are also used to treat infiltrating HCC due to the modest efficacy and high cost of sorafenib treatment (13)(14)(15). TACE is currently considered to be one of the standard treatments for patients with unresectable HCC.…”
Section: Introductionmentioning
confidence: 99%
“…In their series, the majority of patients receiving intraarterial therapy had a Child-Pugh score of A or B, and better results were obtained for patients with a bilirubin level less than 2 mg/dL and an AFP level less than 400 ng/mL at presentation. Similarly, in a recent study, Jang et al (15) suggested that when given to well-selected patients with infiltrative HCC and preserved hepatic function, transarterial chemoembolization is safe and leads to increased survival (>2 years). Overall, systemic chemotherapy is ineffective for patients with HCC (60,61).…”
Section: Treatment and Prognosis For Patients With Infiltrative Hccmentioning
confidence: 92%
“…It has an aggressive course and is associated with a substantially worse prognosis, compared with the nodular HCC subtype (9,10). Infiltrative HCC accounts for approximately 7%-20% of HCC cases (9,(11)(12)(13)(14)(15) and is reported to be commonly associated with hepatitis B virus infection, particularly in Asia (9,16). Patients with infiltrative HCC may have markedly elevated a-fetoprotein (AFP) values (>10,000 ng/mL) (10,13,17).…”
Section: Imaging Modalities For Diagnosis Of Hccmentioning
confidence: 98%